The Advance of Female Artists in Japanese-style Painting: From the Transition of Itō Shōha's Painting Style - Ching, CHEN (Journal of the Society of Art and Design, 2022)
This paper focuses on the historical paintings of the female artist Itō Shōha (1877-1968) in Japanese-style painting, who was born in Ise city. The purpose is to examine Shōha's intention to depict the works in both genres of history and self-portrait, also clarify the relevance between these genres and the changes in her productive backgrounds to identify her advance. It could consider that her painting style roughly separated into three periods: history painting in the late Meiji era, self-portraits in the Taishō era, and returning to history painting in the early Shōwa era. Due to the classification above, I declare the changing of painting styles is Shōha's approach to secure her position in the Japanese painting world where was occupied by male artists. For an instance as Shōha, this paper elucidates the strategy of modern female Japanese painters to maintain themselves' activities in the Japanese painting world.As I inspected the historical paintings of modern Japan through the perspective of gender studies, I found the Japanese historical paintings was male-dominated in the Meiji era. In Shōha's early career, she had created some history paintings and then mainly turned to produce selfportraits during the Taishō era after the selections in the Bunten exhibition.In the Taishō era, Shōha also attempted to depict history paintings genre to participate in the Bunten but failed the selection. As the result, I assume it would be a preferable strategy for Shōha to swift her themes from history to selfportrait through female perspective in order to exhibit in the Bunten.Moreover, it could be observed the obsession and struggle of Shōha as a female artist to seek a feminine style in her historical works. I conclude that the transition of Shōha's painting styles can be regarded as a microcosm for modern female artists who participated in the male-led Japanese painting world.